2016
DOI: 10.18203/2320-1770.ijrcog20164657
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for neonatal hyperbilirubinemia: a case control study

Abstract: Background: Neonatal Hyperbilirubinemia is one of the most common reasons for NICU admissions. The frequency of neonatal jaundice has been on an increase since the last decade. Is the increase due to changes in obstetric practice or drugs? There is no definite reason. This study was undertaken to find out any obstetric characteristics which may contribute to the development of Neonatal Hyperbilirubinemia and which is modifiable.Methods: Record review data from 140 singleton deliveries at the Institute of Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
14
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 6 publications
11
14
1
2
Order By: Relevance
“…The result of this study revealed that neonatal jaundice was positively associated with breastfeeding. This was consistent with the study done in Addis Ababa [ 15 ], Southeast Nigeria [ 20 ], India [ 18 ], and Southern Nepal [ 21 ]. This association is due to the fact that breastfeeding leads to substantial elevation of bilirubin levels during the first few days of life by inhibiting conjugation of bilirubin due to the existence of nonesterified free fatty acid called pregnanediol [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The result of this study revealed that neonatal jaundice was positively associated with breastfeeding. This was consistent with the study done in Addis Ababa [ 15 ], Southeast Nigeria [ 20 ], India [ 18 ], and Southern Nepal [ 21 ]. This association is due to the fact that breastfeeding leads to substantial elevation of bilirubin levels during the first few days of life by inhibiting conjugation of bilirubin due to the existence of nonesterified free fatty acid called pregnanediol [ 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, jaundice was positively associated to obstetric complication. This was correspondent with the study report of Mekelle [ 15 ], Harare [ 23 ], and India [ 18 ]. Birth asphyxia was higher in the jaundiced neonates compared to the controls.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is comparable to the findings of a study conducted in Southern Nigeria [ 13 ]. Our study also confirmed an earlier observation by Menon and Amanullah [ 14 ] and Devi and Vijaykumar [ 15 ] which associated neonatal jaundice with low neonatal birth weight in India. This is further buttressed by the finding of neonates with low birth weight being more likely to develop neonatal jaundice in the logistic regression.…”
Section: Discussionsupporting
confidence: 92%